2000
DOI: 10.1034/j.1600-051x.2000.027005366.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐8 levels and elastase activities in gingival crevicular fluid from chronic adult periodontitis patients

Abstract: Similarities between MMP-8 and elastase probably reflect the fact that both enzymes are associated mainly with neutrophils: MMP-8 levels may have fallen more after treatment because the assay, unlike that for elastase, would most likely not have detected much enzyme bound to alpha-macroglobulin. The immunoassay for MMP-8 is more specific and convenient than functional collagenase assays, and might be suitable for monitoring the periodontal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 10 publications
12
114
0
4
Order By: Relevance
“…[39], polymorphonuclear leukocytes are the main source of so-called salivary MMPs. MMPs derived from inflammatory infiltrate cells, but not stationary cells, are mainly responsible for the destruction of tooth-supporting tissues in the course of chronic periodontitis, previously known as adult periodontitis [10,36,40]. These MMPs include the neutrophil collagenase MMP-8 and gelatinase MMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…[39], polymorphonuclear leukocytes are the main source of so-called salivary MMPs. MMPs derived from inflammatory infiltrate cells, but not stationary cells, are mainly responsible for the destruction of tooth-supporting tissues in the course of chronic periodontitis, previously known as adult periodontitis [10,36,40]. These MMPs include the neutrophil collagenase MMP-8 and gelatinase MMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…3A, 3B). Given the high concentration of collagenase with which we chose to challenge the samples, which was 2 to 6 orders of magnitude higher than the MMP-8 level found in human oral fluids (Liede et al, 1999;Chen et al, 2000;Mäntylä et al, 2003), it comes as no surprise that the untreated demineralized collagen disappeared completely after 1 hr of digestion (Figs. 1B, 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [18] observed that a concentration of MMP-8 in gingival crevicular fluid is positively correlated with the plaque index and bleeding index, whereas the total amount of MMP-8 in GCF is also correlated with the depth of periodontal pockets in patients with periodontitis.…”
Section: Mediators Of Inflammation In Periodontal Diseasesmentioning
confidence: 99%